Characterization of TiO2 Nanofilms Obtained by Sol-gel and Anodic Oxidation - Vera, Maria Laura (2014)
The influence of sol-gel dip-coating and anodic oxidation process parameters to produce thin TiO2 films is studied. As the size of the films is in the order of nanometers (20-140 nm), to obtain a precise measurement of their thickness and analyze their crystalline structures, glancing incidence angle X-ray techniques (X-ray reflectometry and X-ray diffraction) using synchrotron radiation are used. A relationship between the color and thickness of the films was found. This enables the film thickness to be estimated by the film color. In the range of the parameters studied, both techniques produce thin films with smooth surfaces which at most reproduce the surface polished substrate roughness. Independently of the technique, thermally treated films thicker than 30 nm presented different crystalline structures with anatase and rutile phases.